1995
DOI: 10.1523/jneurosci.15-02-01285.1995
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular signal-regulated protein kinases (ERKs) and ERK kinase (MEK) in brain: regional distribution and regulation by chronic morphine

Abstract: Quantitative blot immunolabeling techniques were used to determine the concentrations of ERK1 (M(r) 44 kDa) and ERK2 (M(r) 42 kDa), the two major extracellular signal-regulated protein kinases, in different regions of rat brain. The aggregate ERK concentrations (ERK1 and ERK2) were relatively high in each of the brain regions studied, ranging from approximately 0.35 ng/microgram protein in cerebellum to approximately 1.2 ng/microgram protein in nucleus accumbens. However, differences in the regional distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
134
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(154 citation statements)
references
References 55 publications
20
134
0
Order By: Relevance
“…Animal data suggest that ERK might be involved in regulation by opiate drugs of tyrosine hydroxylase, with protein levels increased in rat "striatum" (the rodent counterpart of the human caudate and putamen) following chronic morphine administration (Ortiz et al 1995;Berhow et al 1996). Our data suggest, however, that any regulation by ERK of tyrosine hydroxylase in the human does not involve changes in actual striatal levels of ERK.…”
Section: Erkmentioning
confidence: 59%
See 2 more Smart Citations
“…Animal data suggest that ERK might be involved in regulation by opiate drugs of tyrosine hydroxylase, with protein levels increased in rat "striatum" (the rodent counterpart of the human caudate and putamen) following chronic morphine administration (Ortiz et al 1995;Berhow et al 1996). Our data suggest, however, that any regulation by ERK of tyrosine hydroxylase in the human does not involve changes in actual striatal levels of ERK.…”
Section: Erkmentioning
confidence: 59%
“…Wakabayashi et al 1995, we measured levels of dopamine metabolites (homovanillic acid, 3-methoxytyramine, dihdroxyphenylacetic acid), serotonin and metabolite 5-hydroxyindoleacetic acid, and noradrenaline. Finally, as experimental animal data show that chronic opiate administration can upregulate striatal concentrations of extracellular signal-regulated kinases (ERKs), signaling molecules that may be involved in the regulation of levels of tyrosine hydroxylase (Ortiz et al 1995;Berhow et al 1996), we also determined striatal concentration of ERK2 in the heroin users. Our biochemical findings suggest that chronic heroin exposure might modestly decrease both dopaminergic and serotonergic function in the human.…”
Section: To Establish Whether Chronic Opiate Exposure Might Impair Brmentioning
confidence: 99%
See 1 more Smart Citation
“…Ortiz and coworkers (Ortiz et al 1995) have reported that chronic morphine treatment selectively increased the levels of ERK1 and ERK2 in locus coeruleus and caudate/putamen. In contrast, they did not find any changes in ERK levels in the other brain regions examined, such as substantia nigra, ventral tegmental area, nucleus accumbens and frontal cortex.…”
Section: Discussionmentioning
confidence: 98%
“…Among different brain regions, hippocampus and some other brain areas have the highest level of ERKs (Ortiz et al, 1995). Borras and colleagues (2006) showed that genistein acts via interaction with estrogen receptors leading to activation of MAP kinases and nuclear translocation of NFĸB, and overexpression of manganese superoxide dismutase (MnSOD) which acts as antioxidant.…”
Section: Discussionmentioning
confidence: 99%